2022
DOI: 10.1155/2022/8441239
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity and Chemical Characterization of Sudanese Bee Honey: Crude Acacia and Its Organic Extracts

Abstract: Honey has recently been rediscovered as an antibacterial and wound-healing natural product. The medicinal properties of honey originate from the floral source used by bees. The objective of the current study was to evaluate the antimicrobial activity of Sudanese crude acacia bee honey and its solvent extracts regarding its biological activity and chemical characterization. To verify the nature of the antibacterial agent(s) of honey, sample (A) Sudanese crude unprocessed acacia bee honey obtained from west of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
3
0
0
1
Order By: Relevance
“…The findings of this investigation can concur with in vitro work by Wadi [54] as they too found honey to be effective at reducing bacterial bioburden for clinical isolates similar to those found in foot and ankle wounds including S. aureus, E. coli and P. aeruginosa . Authors [54] however tested various different honey samples and did not alter pH. They did however compare their findings to common clinically used antibiotics and identified that honey was more effective at controlling bacterial growth [38].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The findings of this investigation can concur with in vitro work by Wadi [54] as they too found honey to be effective at reducing bacterial bioburden for clinical isolates similar to those found in foot and ankle wounds including S. aureus, E. coli and P. aeruginosa . Authors [54] however tested various different honey samples and did not alter pH. They did however compare their findings to common clinically used antibiotics and identified that honey was more effective at controlling bacterial growth [38].…”
Section: Discussionsupporting
confidence: 90%
“…In recent years, greater interest is evident for evaluating the effects of honey on antibiotic resistant organisms, as well as the use of honey as a wound management alternative to antibiotic therapy and other conventional wound dressings [38]. The findings of this investigation can concur with in vitro work by Wadi [54] as they too found honey to be effective at reducing bacterial bioburden for clinical isolates similar to those found in foot and ankle wounds including S. aureus, E. coli and P. aeruginosa . Authors [54] however tested various different honey samples and did not alter pH.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…As Estudos sobre as atividades antioxidantes e antimicrobianas do mel e da própolis foram realizados e reportados há muitos anos por diversos autores (Mandal et al, 2010;Neupane et al, 2014;Wadi, 2014). Também há muitos relatos de atividades da própolis de diversos tipos contra bactérias como a E. coli (Garedew et al, 2004), S. aureus (Lu et al, 2005), Streptococcus sp.…”
Section: Discussionunclassified